2021
DOI: 10.1590/1982-0275202138e190103
|View full text |Cite
|
Sign up to set email alerts
|

Latent structure evidence of the Depression, Anxiety and Stress Scales - Short Form

Abstract: This study aimed to investigate the psychometric properties of the Depression, Anxiety and Stress Scales - Short Form in a Brazilian sample. The instrument was answered online by 250 university students. The following models were tested through Confirmatory Factor Analysis: one-dimensional, three oblique factors, hierarchical, and bifactor. The estimated indices showed a better adjustment for a bifactor model composed of three specific factors and one global factor. Additional statistical analysis, such as exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The answers are given in a Likert-type scale, from "Did not apply to me at all" (0) and "Applied to me very much, or most of the time" (3). The analyses of the psychometric properties performed by Rocha et al (2021) revealed good convergent validity, internal consistency and temporal reliability indicators for the scale in the employed sample. It is possible to identify three specific factors (i.e., depression, anxiety and stress) and a general factor (i.e., negative affectivity) for the DASS-21 latent structure, although the measure is predominantly unidimensional (Rocha et al, 2021).…”
Section: Instrumentsmentioning
confidence: 86%
See 1 more Smart Citation
“…The answers are given in a Likert-type scale, from "Did not apply to me at all" (0) and "Applied to me very much, or most of the time" (3). The analyses of the psychometric properties performed by Rocha et al (2021) revealed good convergent validity, internal consistency and temporal reliability indicators for the scale in the employed sample. It is possible to identify three specific factors (i.e., depression, anxiety and stress) and a general factor (i.e., negative affectivity) for the DASS-21 latent structure, although the measure is predominantly unidimensional (Rocha et al, 2021).…”
Section: Instrumentsmentioning
confidence: 86%
“…After the stage of content validity, the CPQ was responded by a university sample and the scores were submitted to the statistical analysis, in order to examine the instrument's psychometric properties, such as factor structure, internal consistency and validity in relation to other variables. Once the present research is part of a larger range of studies, the same database of Rocha, Hernandez, and Falcone (2021) has been analyzed applying different research questions and different analytical approaches, as suggested by Fine and Kurdek (1994) and by Kirkman and Chen (2011).…”
Section: Studymentioning
confidence: 99%
“…Answers are given in Likert-type scale, from "Did not apply at all" (0) to "Applied a lot or most of the time" (3). Although the presence of specific factors (i.e., depression, anxiety, and stress), the measure is predominantly unidimensional (i.e., negative affectivity) (Rocha et al, 2021).…”
Section: Instrumentsmentioning
confidence: 99%